Cultivation Effects on Organic Matter Concentration and Infiltration Rates of Two Creeping Bentgrass (Agrostis stolonifera L.) Putting Greens. Issue 1 (11th January 2014) - Schmid, Charles J.; Gaussoin, Roch E.; Shearman, Robert C.; Mamo, Martha; Wortmann, Charles S.
Abstract : Soil cultivation is commonly used to manage organic matter (OM) accumulation in golf course putting greens. Our objectives were to determine: (i) if hollow‐tine cultivation is more effective than solid‐tine cultivation at managing OM and water infiltration, (ii) if venting methods are effective at managing OM and water infiltration, and (iii) if venting alters or interacts with effects of early‐ or late‐season cultivation. The study was a 3 × 5 factorial repeated on two 'Providence' creeping bentgrass ( Agrostis stolonifera L.) research putting greens. Tine treatments were hollow‐tine, solid‐tine, or no‐tine cultivation. Venting treatments were Hydroject, PlanetAir, quad needle tine, bayonet tine, or no venting. Soil samples were collected and analyzed for OM content using loss on ignition. Water infiltration rates were determined in situ. After 2 years, there were few consistent differences found among the tine and venting treatments, and there were no significant interactions regarding OM concentration. This response was attributed to the small amount of surface area impacted by cultivation and to the equalization of topdressing quantity across all treatment combinations. Hollow‐tine and solid‐tine cultivation increased infiltration compared with no cultivation. In general, Hydroject treatments increased water infiltration rates more than all other venting treatments regardless of tine treatment.